Wings of tropical finches: interspecific differences in shape are consistent with levels of mobility, but moult and feather fault patterns are more complex. (2nd October 2017) - Franklin, Donald C.; Legge, Sarah; Skroblin, Anja; Heathcote, Joanne; Maute, Kimberly; Schaefer, Douglas J.; Garnett, Stephen T.
ABSTRACT: Birds' wings reflect their life histories, suggesting evolutionary selection for wing shapes and moult strategies. Compared to sedentary species, long-distance migrants have narrower wings (for fast, efficient flight); they have fewer feather faults and avoid moulting flight feathers during migration (to optimise flight surface performance). It is unclear whether these patterns apply to species that fly short-intermediate distances, like tropical nomads. We compared wing shape, feather faulting, and flight-feather moult across five finch species from northern Australia with varying mobility: Pictorella Mannikins ( Heteromunia pectoralis ) and Gouldian Finches ( Erythrura gouldiae ) are highly mobile, nomadic at regional scales; Long-tailed Finches ( Poephila acuticauda ) and Double-barred Finches ( Taeniopygia bichenovii ) are sedentary with local nomadism; Crimson Finches ( Neochmia phaeton ) are sedentary. More mobile species had narrower wings and higher wing loading than relatively sedentary species, and less feather faulting. Variation in moult strategies was complex, but mobile species carried out moult fast, in a short time window, and moulted a single feather at a time. Unexpectedly, Gouldian Finch wings were more suited for fast efficient flight than Pictorella Mannikin wings, and yet they had more feather faulting. Differences in mobility may be a key dimension of niche separation that allows these species to co-exist.